Digital technologies, legal design and the future of the legal profession - Corrales, Marcelo; Fenwick, Mark; Haapio, Helena (Springer, 2019)
Legal Technology – or “Legal Tech” – is disrupting the traditional operations and self-understanding of the legal profession. This chapter introduces the central claim of this book, namely that these developments are having and will continue to have a disruptive effect on the work of lawyers and that adapting to this new operating environment is crucial for legal professionals remaining relevant in an increasingly technology-driven world. This introductory chapter outlines some of the main features of this on-going transformation process, introduces some of the pressures it is creating for lawyers, and provides short summaries of the chapters that comprise this collection.
Keywords: legal tech; blockchain; smart contracts; cryptocurrency; legal design; legal profession; fi=Talousoikeus|en=Business Law|